O jovem como multiplicador das boas práticas agrícolas no município de Agudo, RS, Brasil - Botega, Marcia Palma (2011)
The human exposure to pesticides is a serious public health problem, mainly in developing countries. The rural worker and his family are exposed to several risky situations to their health while performing their activities in the field. When incorrectly used, pesticides can induce contamination to men and the environment. Human and environmental contamination by pesticides is far from being a simple problem mostly due to the diversity of the cultural, economical and social factors involved. Facing the complexity of the theme, the main goal of this study was to capacitate young students, small farmer's children, from the countryside of Agudo, RS, school students from the basic education Professor Willy Roos, to act as information multipliers about the importance of pesticides proper use and its risks to human and environment health, emphasizing the Agricultural Good Practices. Considering the purpose of this research, a questionnaire was applied to illustrate students conceptions to pesticides exposure. It was noted a worrying prospect, since they manifested lack of knowledge about pesticides although having direct and indirect contact with it. Science, technology, society and environment (CTSE) approach was used in order to place the students in the social and cultural environment. Based on this approach, the 'Pesticide' theme was worked in a contextualized manner, generating a greater meaning to the students, showing the practical applications of scientific knowledge. Considering that this work was elaborated with the purpose of educating young information multipliers about Agricultural Good Practices, the main didactic strategies used were reading, text interpretation, groups discussions, study of the environment, collective projects, interaction with the community and college coexistence, wich demanded active participation in the learning and training process. The results showed the need to introduce the theme in school, through a interdisciplinary approach involving biological and natural science teaching relations with the reality of other disciplines like, for example, Mathematics and Chemistry, allowing the students a better understanding of the issues related to health and environment, as well as agricultural extension programs, that leads to technical assistance and information to the community, where the main focus is the rational and safe use of pesticides, ensuring a good quality of life to this population.